2004
DOI: 10.1186/1472-6750-4-15
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the utility of combining Φ29 whole genome amplification and highly multiplexed single nucleotide polymorphism BeadArray™ genotyping

Abstract: Background: Sustainable DNA resources and reliable high-throughput genotyping methods are required for large-scale, long-term genetic association studies. In the genetic dissection of common disease it is now recognised that thousands of samples and hundreds of thousands of markers, mostly single nucleotide polymorphisms (SNPs), will have to be analysed. In order to achieve these aims, both an ability to boost quantities of archived DNA and to genotype at low costs are highly desirable. We have investigated Φ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…For example, Bergen et al [25] examined 49 TaqMan assays with regional GC% ranging from 33 to 65.8% and found a significant correlation with genotyping success. The other predictor of failure, telomere proximity, is also supported by other analyses [10,12]. While haplotypes tagging strategies [26] cannot avoid the telomeres, in studies using amplified DNA it seems advisable to avoid SNPs in G/C rich regions.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Bergen et al [25] examined 49 TaqMan assays with regional GC% ranging from 33 to 65.8% and found a significant correlation with genotyping success. The other predictor of failure, telomere proximity, is also supported by other analyses [10,12]. While haplotypes tagging strategies [26] cannot avoid the telomeres, in studies using amplified DNA it seems advisable to avoid SNPs in G/C rich regions.…”
Section: Discussionmentioning
confidence: 91%
“…F29 Polymerase-based multiple-strand displacement wga (MDA) currently appears to be the most promising of these techniques. Multiple displacement amplification (MDA) has already been assessed using high-throughput DNA arrays on a limited number of samples [7,8,[11][12][13]. These studies report an excellent concordance of genotypes between pairs of genomic DNA (gDNA) and amplified DNA (wgaDNA) as well as good genome coverage despite the loss of a limited number of loci and regions that failed to amplify [11,13].…”
Section: Introductionmentioning
confidence: 98%
“…Here, we used a WGA based on the MDA technology that employs the phi29 DNA polymerase and random primers to amplify gDNA without thermocycling [ 40 , 41 ]. Several studies revealed that MDA can amplify the genome with higher uniformity, longer length, and less bias compared with PCR-based WGA methods [ 41 , 42 , 43 , 44 , 45 ]. Therefore, MDA-based WGA has been shown to be the best method to obtain high quality cfDNA for different applications, such as the NGS [ 44 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, this study is the first one that made use of the variable multiplexing ability of the same genotyping technology to study the relationship between genotyping performance and multiplexing level of the assays using wgaDNA, and to examine whether the storage of wgaDNA would reduce the genotyping efficiency. Indeed, existing studies [15] , [19] [22] have successfully addressed the question of whether wgaDNA could be used in high-throughput array-based assays, e.g., Affymetrix and Illumina genotyping chips. High concordance was detected between wgaDNA and gDNA, highlighting the reliability of using wgaDNA for high-throughput genotyping with good accuracy.…”
Section: Discussionmentioning
confidence: 99%